1986
DOI: 10.2307/3430312
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the Mutagens in Cooked Beef

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org. . The National Institute of Environmental Health Sciences (NIEHS) and Brogan & Partners are collaborating with JSTOR to digitize, preserve and extend access to Environmental He… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
44
0

Year Published

1990
1990
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(45 citation statements)
references
References 1 publication
1
44
0
Order By: Relevance
“…Gross (1990) found 23.5 and 48.5 ng/g PhIP in steak fried at 190C in a Teflon pan for 6 and 13 min, respectively. While Murray et al (1993) reported 0.6 ng/g PhIP in beef fried at 225C for 12 min, Felton et al (1986) stated the finding 15 ng/g PhIP in ground beef, which was fried for 11 min at 300C, and Gross et al (1993) stated that meatballs grilled at 250-270C for 19 min contained PhIP at a level of 3.1 ng/g. Abdulkarim and Smith (1998) reported that PhIP concentration of 5% fat meatballs fried at 190C for 10 min was 0.85 ng/g, and PhIP value of those fried at 230C for 15 min was 1.09 ng/g.…”
Section: Hca Contents Of Chopsmentioning
confidence: 99%
“…Gross (1990) found 23.5 and 48.5 ng/g PhIP in steak fried at 190C in a Teflon pan for 6 and 13 min, respectively. While Murray et al (1993) reported 0.6 ng/g PhIP in beef fried at 225C for 12 min, Felton et al (1986) stated the finding 15 ng/g PhIP in ground beef, which was fried for 11 min at 300C, and Gross et al (1993) stated that meatballs grilled at 250-270C for 19 min contained PhIP at a level of 3.1 ng/g. Abdulkarim and Smith (1998) reported that PhIP concentration of 5% fat meatballs fried at 190C for 10 min was 0.85 ng/g, and PhIP value of those fried at 230C for 15 min was 1.09 ng/g.…”
Section: Hca Contents Of Chopsmentioning
confidence: 99%
“…If so, other fried foods could also be of interest with regard to urothelial cancer. Data on mutagens formed during cooking and of mutagenic activity in the urine following meals of fried meat are rapidly accumulating (Lijinsky and Shubik, 1964; Sugimura and Sato, 1983;Dolara et al, 1984;Baker et al, 1986;Felton et al, 1986;Overvik, 1989).…”
mentioning
confidence: 99%
“…The two groups of HAAs are amino-carbolines and aminoimidazo-azaarenes which are most commonly referred to as AIAs (Hatch et al 1989). These compounds are formed by the high-temperature pyrolysis of the amino acids and creatinine present in meats (Felton et al 1986). The structure of 10 such HAAs are shown in Fig.…”
Section: Introductionmentioning
confidence: 99%